2012
DOI: 10.1186/1477-5956-10-15
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the vitreous proteome in proliferative diabetic retinopathy

Abstract: BackgroundDiabetes can lead to serious microvascular complications such as proliferative diabetic retinopathy (PDR), which results in severe vision loss. The diabetes-induced alterations in the vitreous protein composition in diabetic patients with PDR may be responsible for the presence of PDR. The vitreous humour can be utilised in a variety of studies aimed toward the discovery of new targets for the treatment or prevention of PDR and the identification of novel disease mechanisms. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 54 publications
1
45
0
1
Order By: Relevance
“…The EGCs network has trophic and protective functions toward enteric neurons and is fully implicated in the integration and the modulation of neuronal activities [33][34][35] . In addition, EGCs within the ENS have a significant role in forming a diffusion barrier around the capillaries surrounding ganglia similar to that of bloodbrain barrier [3,15,[36][37][38] .…”
Section: Non-neuronal Cells In the Ensmentioning
confidence: 99%
“…The EGCs network has trophic and protective functions toward enteric neurons and is fully implicated in the integration and the modulation of neuronal activities [33][34][35] . In addition, EGCs within the ENS have a significant role in forming a diffusion barrier around the capillaries surrounding ganglia similar to that of bloodbrain barrier [3,15,[36][37][38] .…”
Section: Non-neuronal Cells In the Ensmentioning
confidence: 99%
“…3,4 Several studies have indicated that there is a significant increase in the levels of proangiogenic and proinflammatory factors and cytokines (e.g., vascular endothelial growth factor, IL-8, TNF-a, IL-6, and IL-1b) in the vitreous of a patient with diabetic retinopathy. [40][41][42][43] These findings have led to the emergence of several novel treatment modalities based on the administration of antivascular endothelial growth factor agents and corticosteroids to the diseased retina. 44,45 Corticosteroids are an attractive option due to their broad range of actions including anti-inflammatory and antiangiogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although chymotrypsin is a digestive system enzyme, it degrades proteins hydrolytically in a manner similar to enzymes present in ocular tissues including the vitreous humor [17,35]. Proteomic analyses has confirmed the presence of a number of enzymes in the vitreous humor such as carbonic anhydrase, the glutathione peroxidase or the prostaglandin D2 synthase [36], and 51 proteases, some of which show increases in diseases like the diabetic retinopathy [37][38][39][40]. Contrary to the degradation of PLGA [1], which takes place in the bulk via cleavage of its backbone ester linkages into oligomers and finally monomers [13], degradation of PEA fibrils appears to take place by surface erosion, suggesting that barrier properties of PEA matrix will be preserved during the entire life-time of the implant [22], a characteristic that would allow PEAs to be used for the fabrication of long-term, controlled release devices.…”
Section: Effect Of Chymotrypsin On Fibril Surface Morphologymentioning
confidence: 99%